Peran Collection dalam Strategi Meminimalisir Risiko Kredit Macet pada PT. BPR Wutama Artha Jaya Jember - Mohammad Mirza Pratama; M Nur Cholis (Lembaga Yasin AlSys, 2026)
Bad loans or Non-Performing Loans (NPLs) are one of the significant problems in banking because they can reduce banks’ income and financial performance, including at PT BPR Wutama Artha Jaya Jember. This condition occurs when customers are unable or unwilling to fulfill their credit payment obligations in accordance with the agreed contract. This study aims to analyze the role of collection in handling customers experiencing bad loans and to identify the risk management strategies used in handling bad loans at PT BPR Wutama Artha Jaya Jember. This study used a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data collection, data reduction, summarization, and report preparation. Data validity was ensured through data triangulation. The results showed that collection plays a role not only as the party responsible for debt collection but also as the implementer of monitoring, communication, and persuasive approaches to customers. In practice, the handling of bad loans needs to consider the optimization of credit analysis through the application of the prudential principle based on the 5C principle in credit risk assessment. The factors causing bad loans were identified as originating from internal and external factors. The risk management strategies used included risk identification, measurement, control, and mitigation, as well as the implementation of the 3R strategy, namely rescheduling, reconditioning, and restructuring, as the main effort in handling bad loans. The conclusion of this study affirms that the optimal role of collection and the implementation of systematic risk management strategies contribute to minimizing the risk of bad loans in rural banks.